Hard and soft tissue alterations during the healing stage of immediate implant placement and provisionalization with or without connective tissue graft: A randomized clinical trial. (28th June 2020) - Jiang, Xi; Di, Ping; Ren, Shuxin; Zhang, Yu; Lin, Ye
Abstract: Aims: To evaluate the hard and soft tissue alterations of immediately placed and provisionalized implants with or without connective tissue graft (CTG). Materials and Methods: Single unsalvageable maxillary incisors were replaced with immediately placed and provisionalized implants in 42 participants. The patients were randomly assigned to receive simultaneous CTG (test group) and not receive CTG (control group). Digital impression and cone‐beam computed tomography images were obtained before extraction and after 6 months. Mid‐facial gingival margin migrations, soft tissue contour changes and hard tissue remodelling were analysed and compared between the two groups using three‐dimensional superimposition method. Results: Forty participants completed the study. The test group showed significantly less buccal tissue collapse in the area 2–5 mm apical to the gingival margin. In both groups, the mid‐facial gingival margin migrated in an apico‐palatal direction and the socket void, except for a triangular space in the bucco‐coronal region, demonstrated radiographic new bone formation without statistically significant differences. Conclusions: The CTG used with immediate implant placement and provisionalization could compensate for the facial tissue collapse, but it did not benefit maintenance of the mid‐facial gingival margin position during the 6‐month follow‐up. New bone formation observed radiographically can be expected in most areas of the socket void, regardless of CTG use (ChiCTR‐1900028494).